抜歯後疼痛に対するJNS013（トラマドール塩酸塩／アセトアミノフェン配合錠）の臨床評価－ 各配合成分の単独投与との二重盲検比較試験 - 中嶋, 頼俊; 覚道, 健治; 小村, 健; 金子, 明寛; 山下, 徹郎; 坂田, 秀雄; 平木, 昭光; 新谷, 悟; 久保田, 英朗; 渡貫, 圭; 山本, 英雄; 今井, 裕; et al. (日本口腔外科学会雑誌, 2012)
We assessed the clinical significance of the combined preparation JNS013 and the analgesic efficacy and safety of a single oral dose of JNS013 （Tramadol hydrochloride/acetaminophen combination tablets） as compared with a single dose of tramadol hydrochloride （TRAM） or acetaminophen （APAP） in patients who had pain associated with extraction of a mandibular impacted third molar in a multicenter, double-blind, randomized, active-controlled, parallel-group comparitive study. Efficacy and safety were evaluated in a total of 328 patients who were given the study drugs （JNS013 group: 132 patients, TRAM group: 66 patients, APAP group: 130 patients）. As for the primary endpoint of efficacy, the means ± standard deviations of the total pain relief scores from 0 to 8 hours after administration of the study drugs （TOTPAR 0-8h） were 17.7 ± 7.91 in the JNS013 group, 12.4 ± 8.36 in the TRAM group, and 13.3 ± 8.07 in the APAP group, indicating a significantly higher value in the JNS013 group than in the TRAM and APAP groups. On safety analyses, at least 1 adverse event occurred in 62.1％ （82/132） of patients in the JNS013 group. Major adverse events occurring in the JNS013 group included somnolence 29.5％, nausea 15.2％, dizziness 9.1％, and blood bilirubin increased 9.1％. The severities of most of these adverse events were mild. The symptoms and incidence of adverse events in the JNS013 group were generally similar to those in the TRAM group, while the incidence in the JNS013 group was higher than that in the APAP group. The present study showed that JNS013 was more effective for the management of post-tooth-extraction pain than either uncombined TRAM or APAP, supporting the clinical significance of combination. In addition, the usefulness of the drug for post-tooth-extraction pain was confirmed. JNS013 is expected to provide a new alternative for pain control in the fields of dentistry and oral surgery.